Benign and Malignant Soft Tissue Tumors of Extremities in Adults at Thammasat University Hospital - Hareerak, Thanapa; Kintarak, Jutatip (Asian Medical Journal and Alternative Medicine, 2021)
Objectives: To study the number of cases and the clinicopathological correlation of soft tissue tumors in extremities in adults at Thammasat University Hospital. Method: Descriptive retrospective study, 187 cases of soft tissue tumor in extrmities of adult patients (more than 14 years old) whom undergone at least marginal excisions, and been diagnosed with soft tissue tumors, as per the World Health Organization classification of tumors of soft tissue and bone (2013), during the 3-year period, 1 January 2016 - 31 December 2018. Result: Benign soft tissue tumors accounted for 95.7% of cases, while only 4.3% were attributed to malignant ones. The ratio of female to male patients in the study was 1.03:1, while the female to male ratio among those patients with malignant tumors was 1.67:1. The mean age of patients was 52.3 years. The common age of those with malignant tumors was over 40 years old. Malignant tumors were predominant in the lower extremities, with the size of more than 5 cm in greatest dimension, and located in the deep-seated layer. Conclusion: The number of benign soft tissue tumors is greater than the of sarcomas. The most common benign tumor is lipoma, while the most common malignant one is leiomyosarcoma.